Camk2n1 Is a Negative Regulator of Blood Pressure, Left Ventricular Mass, Insulin Sensitivity, and Promotes Adiposity. Issue 3 (September 2019) - Alfazema, Neza; Barrier, Marjorie; de Procé, Sophie Marion; Menzies, Robert I.; Carter, Roderick; Stewart, Kevin; Diaz, Ana Garcia; Moyon, Ben; Webster, Zoe; Bellamy, Christopher O.C.; Arends, Mark J.; Stimson, Roland H.; et al.
Abstract : Metabolic syndrome is a cause of coronary artery disease and type 2 diabetes mellitus. Camk2n1 resides in genomic loci for blood pressure, left ventricle mass, and type 2 diabetes mellitus, and in the spontaneously hypertensive rat model of metabolic syndrome, Camk2n1 expression is cis-regulated in left ventricle and fat and positively correlates with adiposity. Therefore, we knocked out Camk2n1 in spontaneously hypertensive rat to investigate its role in metabolic syndrome. Compared with spontaneously hypertensive rat, Camk2n1 −/− rats had reduced cardiorenal CaMKII (Ca 2+ /calmodulin-dependent kinase II) activity, lower blood pressure, enhanced nitric oxide bioavailability, and reduced left ventricle mass associated with altered hypertrophic networks. Camk2n1 deficiency reduced insulin resistance, visceral fat, and adipogenic capacity through the altered cell cycle and complement pathways, independent of CaMKII. In human visceral fat, CAMK2N1 expression correlated with adiposity and genomic variants that increase CAMK2N1 expression associated with increased risk of coronary artery disease and type 2 diabetes mellitus. Camk2n1 regulates multiple networks that control metabolic syndrome traits and merits further investigation as a therapeutic target in humans. Abstract : Supplemental Digital Content is available in the text.